An Analysis of Lexical Bundles in Research Articles: Examples from Natural and Social Sciences - Zulyanputri, Annur Karima (JOMANTARA, 2024)
This present research investigates the use of lexical bundles in research articles across different disciplinary areas: natural science and social science. The results showed that there are some differences in the use of lexical bundles between disciplines in the term of frequency, structures, and functions. We found that the frequency of lexical bundles can vary between natural science and social science RA. For example, the lexical bundle "in the learning process" is more common in natural science, while the lexical bundle "on the other hand" is more common in social science. Based on the structural forms, the most common structural form of lexical bundles in natural science RA is verb-based. While the most common structural form of lexical bundles in social science RA is prepositional-based. The contradiction suggests that in terms of structure, there are differences between natural and social science RA writing styles, how the authors establish arguments, and also present results. Meanwhile from the functional classifications, we can conclude that both types of RA have the same order in terms of the frequency of the functional use, with research-oriented bundles being the most frequent. The findings can be used to improve the readability of research articles in one discipline, as well as to help researchers learn the conventions of writing in one discipline.